2021
DOI: 10.3390/antiox10071042
|View full text |Cite
|
Sign up to set email alerts
|

Salvigenin, a Trimethoxylated Flavone from Achillea Wilhelmsii C. Koch, Exerts Combined Lipid-Lowering and Mitochondrial Stimulatory Effects

Abstract: Phytochemical analysis of the Iranian plant Achillea wilhelmsii led to the isolation of 17 pure secondary metabolites belonging to the classes of sesquiterpenoids and phenolics. Two of these compounds, named wilhemsin (7) and wilhelmsolide (9), are new sesquiterpenoids, and the first shows undescribed structural features. Their structures were elucidated through extensive spectroscopic analysis, mainly based on 1D and 2D NMR, and chemical derivatization. Starting from plant traditional use and previous reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
(87 reference statements)
1
13
0
Order By: Relevance
“…The plant belongs to Asteraceae or Compositae family, and the genus Achillea comprises over 120 species worldwide [5]. The plant is widely distributed in Asia particularly in Pakistan, Iran, and India [6]. The word Achillea was derived from the Greek word Achilles, which means "hero," and was mostly used to cure various diseases during battles [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant belongs to Asteraceae or Compositae family, and the genus Achillea comprises over 120 species worldwide [5]. The plant is widely distributed in Asia particularly in Pakistan, Iran, and India [6]. The word Achillea was derived from the Greek word Achilles, which means "hero," and was mostly used to cure various diseases during battles [7].…”
Section: Introductionmentioning
confidence: 99%
“…The plant is best known for its pleasant fragrant aroma and traditionally used for treating a variety of health problems by local community [8]. Achillea wilhelmsii contains various chemical constituents including alkamides, alkaloids, carvacrol, linalool, αand β-pinene, borneol, sesquiterpenoids (wilhemsin and wilhelmsolide), monoterpenoids, caryophyllene, rutin, thujene, 1,4-cineol, and camphor [6]. It has been shown that Achillea contains bitter aromatic substances having imperative effects on nervous system and neurological diseases such as epilepsy, neurasthenia, and seizures [9].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the studies where salvigenin and esculetin present low antioxidant activity. Indeed, salvigening is reported with lipid-lowering and mitochondrial-stimulating activity, while esculentin shows anti-inflammatory, anti-apoptotic, anticancer, antidiabetic, and neuroprotective activities [ 37 , 38 ]. The antimicrobial causality analysis shows that the compounds with the most significant influence on the MRSA and E. faecalis inhibition are chlorogenic acid and esculentin, which are metabolites that are reported as compounds with an antibiotic capacity on gram-positive bacteria [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ferulic acid can ameliorate hepatic inflammation and modulate specific gut microbiota and genes involved in TG and TC metabolism ( Ma et al, 2019 ; Wu et al, 2021 ). Salvigenin improve the metabolic syndrome symptoms by decreasing lipid levels and stimulating mitochondrial functionality and it also help cells to survive by inhibiting apoptosis and enhancing autophagy ( Rafatian et al, 2012 ; Serino et al, 2021 ). Saikosaponin A, modulate glycerolipid metabolism role by regulating Lipe and Lipg and transcription factors peroxisome proliferator-activated receptor alpha (PPARa) ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%